A escola operária Horácio Hora - Ribeiro, Alessandro Cardoso (2023)
The presente essay has its objectiva to show the actions and limits of scholl Horácio Hora, during the first republic. Being the working class education the object of this essay, it is possible to realize that even tho ugh the attempt to transform the education in an instrument of politization and organizition of the working class from Sergipe during the first republic. This first republic was for everyones´s suprise, had an education system that had as its main purpose to maintain the power of the store owners. This conclusion can be reached because both the statute of the working class from Sergipe and the inner regiment of worker´s scholl functioned inside the current order.